PERBANDINGAN KADAR TROMBOSIT PADA PEMBENDUNGAN VENA SELAMA 1 MENIT DAN 2 MENIT: COMPARISON OF PLATTLE LEVELS IN VEIN DAMMING FOR 1 MINUTE AND 2 MINUTES - ari ardiyanto sardi; Sabarina Elfrida Manik; Dian Rachma Wijayanti (Jurnal SainHealth, 2024)
Phlebotomy is the process of drawing blood from the circulatory system through a puncture to obtain a sample. Venous blood collection is done using a tourniquet as a damming device that serves to see the vein under the skin tissue. In adults, one of the veins used is the cubital fossa and in infants using the superficial jugular vein or in the superior sagittal sinus. Platelets are disk-shaped cells with a diameter of 2-5 mm. Under normal circumstances, the number of platelets is about 150,000-450,000 / ml of blood and its life span is about 1- 2 weeks or about 8 days. Platelets are made of phospholipid substances that are important for clotting, maintaining the integrity of blood vessels and repairing damaged small blood vessels. The purpose of this study was to determine the comparison of platelet levels in vein damming at 1 minute and 2 minutes. This study was conducted in the MM2100 industrial area, samples obtained from employees who did Medical Check Up and obtained as many as 30 respondents and 60 samples. The results showed that employees in the MM2100 industrial area with average platelet levels of 274,133/µl of blood at 1 minute and average platelet levels of 278,266/µl of blood at 2 minutes. This study uses the Paired Sample T-Test method, the results obtained with a sig value of 0.229 which means there is no difference in the damming time of 1 minute and 2 minutes on platelet levels.